2018
DOI: 10.1051/0004-6361/201731892
|View full text |Cite
|
Sign up to set email alerts
|

Solar activity over nine millennia: A consistent multi-proxy reconstruction

Abstract: Aims. The solar activity in the past millennia can only be reconstructed from cosmogenic radionuclide proxy records in terrestrial archives. However, because of the diversity of the proxy archives, it is difficult to build a homogeneous reconstruction. All previous studies were based on individual, sometimes statistically averaged, proxy datasets. Here we aim to provide a new consistent multiproxy reconstruction of the solar activity over the last 9000 years, using all available long-span datasets of 10 Be and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 90 publications
7
108
0
2
Order By: Relevance
“…The cosmogenic nuclide of beryllium 10 ( 10 Be) measured in ice cores is an indirect proxy for past solar activity (e.g., Bard et al, 1997;Beer et al, 1990;Berggren et al, 2009;Cauquoin et al, 2014;Delaygue & Bard, 2011;Horiuchi et al, 2008;Raisbeck et al, 1990;Steinhilber et al, 2012;Wu et al, 2018) and for geomagnetic excursions or reversals (e.g., Beer et al, 1988;Finkel & Nishiizumi, 1997;Raisbeck et al, 2017Raisbeck et al, , 2006Yiou et al, 1997). In the atmosphere it is produced from spallation reactions on oxygen and nitrogen atoms induced by primary cosmic rays, whose flux is modulated by the magnetic fields of the Earth and the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…The cosmogenic nuclide of beryllium 10 ( 10 Be) measured in ice cores is an indirect proxy for past solar activity (e.g., Bard et al, 1997;Beer et al, 1990;Berggren et al, 2009;Cauquoin et al, 2014;Delaygue & Bard, 2011;Horiuchi et al, 2008;Raisbeck et al, 1990;Steinhilber et al, 2012;Wu et al, 2018) and for geomagnetic excursions or reversals (e.g., Beer et al, 1988;Finkel & Nishiizumi, 1997;Raisbeck et al, 2017Raisbeck et al, , 2006Yiou et al, 1997). In the atmosphere it is produced from spallation reactions on oxygen and nitrogen atoms induced by primary cosmic rays, whose flux is modulated by the magnetic fields of the Earth and the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it seems that some amplifying terrestrial effect are needed to explain the magnitude of the observed glacier movements. It has to be seen whether the recent detailed analysis of solar activity [50] will allow one to draw more definite conclusions about the influence of the sun on the glacier movement during the Holocene.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Bond et al (2001) argued that these colder episodes were driven by changes in solar insolation (cf. Wanner and Bütikofer, 2008;Wanner et al, 2011), notwithstanding the fact that total solar irradiance did not vary by more than ±0.15% over this period (Vieira et al, 2011;Roth and Joos, 2013;Wu et al 2018). Other paleoceanographic studies have been unable to reproduce the record of ice-rafting reported in Bond et al, (1997) (e.g.…”
Section: Introductionmentioning
confidence: 86%